Foreign-born and US-born black women: differences in health behaviors and birth outcomes. - Cabral, H (1990)
We studied health behaviors and birth outcome among 201 foreign-born and 616 US-born Black women receiving prenatal care at Boston City Hospital. Foreign-born women had better pre-pregnancy nutritional status and prenatal health behaviors, and their infants had greater intrauterine growth. Black women are not a homogeneous group; culture and ethnicity, in addition to other variables, must be considered in the study of their birth outcomes.